2021
DOI: 10.1177/20499361211027390
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glycohemoglobin is linked to critical illness in COVID-19: a retrospective analysis

Abstract: Background: Several studies have explored hospitalization risk factors with the novel coronavirus disease 2019 (COVID-19) infection. Our goal was to identify clinical characteristics outside of laboratory or radiologic data associated with intubation or death within 7 days of admission. Methods: The first 436 patients admitted to the University of Colorado Hospital (Denver metropolitan area) with confirmed COVID-19 were included. Demographics, comorbidities, and select medications were collected by chart abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…By contrast, research by Zhang et al (42), revealed no significant correlation between concomitant hypertension and severity of COVID-19. Conversely, hypertension was the comorbidity most commonly associated with an increased risk of severity in individuals with COVID-19 (27,28,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Immune system disruption in patients with T2DM and hypertension increases the risk of infection with COVID-19 (46).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…By contrast, research by Zhang et al (42), revealed no significant correlation between concomitant hypertension and severity of COVID-19. Conversely, hypertension was the comorbidity most commonly associated with an increased risk of severity in individuals with COVID-19 (27,28,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Immune system disruption in patients with T2DM and hypertension increases the risk of infection with COVID-19 (46).…”
Section: Discussionmentioning
confidence: 98%
“…The present study may be useful in providing insights into the severity of COVID-19 and comorbities, particularly T2DM. Several studies found a correlation between severity of COVID-19 and increased inflammatory responses (34,42,45,48,49), while other studies determined that glycemic control was associated with patient outcome (24,(51)(52)(53), and certain others found that there is a correlation between hypertension, diabetes and COVID-19 infection (22,27,28,(43)(44)(45). The aforementioned are independent studies, and while they support each other and the findings of the present study, to the best of our knowledge, research comparing a combination of several factors has yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation